Research on clock synchronization of ad hoc networks - DONG Chao; TIAN Chang; NI Ming-fang (Tongxin xuebao)
As the variety of ad hoc networks applications and synchronization requirements, none synchronization proto-col can fit all the conditions. Based on the analysis of the difficulty of networks clock synchronization, the particularity of clock synchronization protocols for different networks applications was discussed and the typical clock synchronization protocols proposed for these applications were introduced. Finally, some further research problems for ad hoc networks clock synchronization were analyzed primarily.